Character Education Through Learning In Al-Ikhlas Al-Quran Education Center Nampirejo Batanghari - Yuyun Yunita; Abdul Mujib (Ri'ayah: Jurnal Sosial dan Keagamaan, 2023)
Islamic education is one of the main pillars of character education. Character education will grow well if it starts with instilling a good Islamic soul. Islamic education learning has started in elementary Centers, through Islamic education learning a student is taught aqidah as the basis of religion. Learning at the Al-Quran Education Center provides a lot of strengthening of children's character and understanding of religion which can be a provision for life in the future. The Al-Quran Education Center is a level of education for children which is held in order to develop the personality and knowledge of children as well as education to read the Al-Qur'an. The development of TPA began in the 1990s with the discovery of various methods of reading the Qur'an and Iqro. Landfill upgrade until now shows the increasing level of public awareness of the importance of Islamic values ​​for the foundation and future of their children.